PATRONASE DAN MODULAR PADA CALONLEGISLATIF PEREMPUAN NEWCOMER (Jurnal Nawala Politika, 2023)
This research aims to determine how patronage clientelism and political modularity are in the 2019 legislative elections in Abiansemal District. This study is framed using the theory of patronage clientelism and theory of modular parties as an analytical tool for the problems in this research. The research method used in this research is qualitative descriptive research with primary and secondary data usage, because it describes and illustrates phenomena that exist, both natural and human engineering, which pay more attention to the characteristics, quality, interrelationships between activities in relation to patronage relationships. and modular in legislative elections.The results of this study are: first, the relationship between actors and voters (patron-client) tends to function as a use for candidate identification and vote-seeking based on kinship relationships and reciprocal relationships between actors and voters. Second, Ni Luh Sekarini used the role of brokers and parties (modular parties) in the process of winning through mass mobilization. Third,. theory of modular parties dominates in terms of proving and utilizing research findings Keywords : Ni Luh Sekarini, Patronage-Clientelism, Modular parties